THE MECHANISM OF EXECUTION OF THE JUDGE'S DECISION IN A SIMPLE LAWSUIT - Agus Hartawan Firmansyah; Nurjannah Septyanun; Yulias Erwin (Jurnal Ilmiah Advokasi, 2024)
Community life is inseparable from conflicts of private interest between one legal subject and another legal subject, both between person to person, person to legal entity or legal entity to legal entity. The conflict that occurs requires a dispute resolution and enforcement of civil law which now seems protracted and long-winded because of the long process of resolving cases in court so that the application of the principle of fast, simple, and light costs cannot be realized. The community's need for justice in resolving a dispute at low cost and with fast events. This research uses the Normative legal research method using a Qualitative approach. The results of the study that, Dispute resolution at low cost and with fast events, the Supreme Court applies a simple lawsuit based on Supreme Court Regulation Number 2 of 2015 jo PERMA No 4 of 2019 concerning Procedures for Resolving Simple Claims. This Supreme Court regulation is a major step from the Supreme Court to realize the resolution of cases according to the principle of fast, simple and low cost. The implementation of simple lawsuit decisions is the same as the implementation of ordinary civil case decisions, which are carried out voluntarily and execution.Keywords: Simple lawsuit, Judge's decision, and Implementation of the decision